From Moses to the daughters of Zelophehad: patristic reception of biblical characters and texts - Elliott, Mark W.; Siquans, Agnethe (Antike Schriftauslegung, 2024)
This volume explores the patristic treatment of biblical characters and character. Patristic authors interpret the Bible and use it in the development of their theology and in debates on theological, Christological and ecclesiological issues. The individual contributions deal with the view of the Church Fathers on the person of Moses, with Maximus Confessor’s depiction of King Hezekiah, with the interpretation of the texts on the daughters of Zelophehad, with the theological interpretation of the story of Elijah on Mount Horeb, with the spiritual interpretation of the Psalms in Jerome’s letters, the significance of the Psalms for the Christological argumentation in Cassiodorus, the interpretation of the Book of Job in various commentaries, the Christological interpretation of the Twelve Prophets and the understanding of the nation angels in John Chrysostom. The volume concludes with a summarising response.